Foot sensation status of Malay women with type 2 diabetes mellitus - Yong, Siew Ping; Siti Balkis Budin; Sazlina Kamaralzaman (penerbit ukm, 2012)
This study aimed to identify the foot sensory status of Malay women with type 2 diabetes mellitus and to determine its relation with: demographic factors, glycated haemoglobin level in plasma, and body mass index. A cross-sectional study was conducted on 71 Malay women with type 2 diabetes mellitus who attend three health clinics in Hulu Langat District, Selangor. Foot sensation was assessed using the Semmes-Weinstein Monofilament 5.07 in nine locations on the plantar and dorsal of the feet. Loss of protective sensation was defined as inability to sense the monofilament in one or more sites of either foot. This study found that 56.3% of women had loss of protective sensation, with common sites being the heel, fifth metatarsal head, lateral mid-foot and little toe. Duration of diabetes mellitus were significantly related to foot sensation. The age, HbA1C level and body mass index did not show any significant correlation. Loss of protective sensation may lead to serious foot complication and therefore early screening involving multidisciplinary team is essential for prevention.